Increasing Interest, Results and Ability to Listen to Stories Using Audio Visual Media in Elementary Schools - Suryaputra, Angga; Bagiya, Bagiya; Ratnaningsih, Arum (Jurnal Pendidikan Amartha, 2023)
This study aims to increase students' interest and learning outcomes using audio-visual media on the listening skills of class III SD Negeri Grantung students. This study uses Classroom Action Research (CAR), which consists of two cycles. Each cycle consists of two meetings. The subjects in the research were Grade III students at SDN Grantung, totaling 22 students. Data collection methods used are interviews, observation and documentation with quantitative analysis techniques. The media used in this research is audio-visual. The stages are 1) The teacher plays an audio-visual video 2) students listen to the story 3) the teacher evaluates. Based on the results of the research that has been done about students' interest in learning increasing, it can be seen based on the results of the application of the method of listening to stories using audio-visual in the pre-cycle to get an average of 72.75%, then in cycle I get an average of 75.775% and cycle II get average 88.25% included in the high criteria. Furthermore, student learning outcomes increased from pre-cycle obtaining an average of 50%, then in the first cycle stage there was an increase with an average of 70.5% entering the medium category but in cycle II experiencing a fairly good increase to 87.5% entering in very good criteria.